Agro-Climatic Suitability Evaluation for Saffron Production in Areas of Western Himalaya - Kothari, Deepak; Thakur, Meenakshi; Joshi, Robin; Kumar, Amit; Kumar, Rakesh (Frontiers in Plant Science, 2021)
Saffron (Crocus sativus L.) is an expensive spice crop cultivated successfully in Iran, Afghanistan, India, Greece, Morocco, Spain, and Italy. The present study was conducted during 2018-19 and 2019-20 to evaluate the morphological, yield and quality parameters of saffron in six different regions of non-traditional areas of western Himalayas. The two experimental factors were ‘‘year’’ and ‘‘location’’. The experiment was conducted in factorial randomized block design with three replications. Yield attributes viz., number of flowers, fresh flower yield, fresh stigma yield and dry stigma yield were significantly higher in location L3 as compared with other geographical locations. Dry stigma yield in location L3 was higher by 50.0, 41.2, 33.3, 14.3, and 9.1% compared with locations L6, L5, L1, L4, and L2, respectively. These were characterized by the appropriate climatic conditions viz., high altitude, sandy-loam texture of the soil, optimum temperature, lesser relative humidity and total rainfall demonstrating that it is possible to cultivate this spice even in non-traditional areas of western Himalayas. Positive correlations were established for stigma yield with increased altitude and lesser rainfall. Secondary metabolites viz., crocin and picrocrocin increased significantly with the increase in altitude; however, a reverse trend was recorded for safranal content. Total phenolics and flavonoids were significantly higher in the geographical location of Kinnaur, H.P. (L1) and Bharmour, H.P. (L4). In conclusion, the assessment of different geographical locations and soil types is particularly necessary to produce saffron production and its qualitative traits. Based on current findings, saffron can be grown successfully in some non-traditional locations of the western Himalayan regions.